Preclinical and clinical studies of a tumor targeting IL-12 immunocytokine - Minnar, Christine M.; Lui, Grace; Gulley, James L.; Schlom, Jeffrey; Gameiro, Sofia R. (Frontiers in Oncology, 2024)
The clinical success of immune checkpoint inhibitors (ICIs) has demonstrated the promise and challenges of cancer immunotherapy. There is an unmet need to develop novel cancer therapies that can provide clinical benefit for most patients with solid malignancies, which harbor innate or acquired resistance to ICIs. Interleukin-12 (IL-12) is a promising cytokine for cancer therapy given its direct stimulatory effects on innate and adaptive immunity. However, unfavorable pharmacokinetics and a narrow therapeutic index render recombinant IL-12 (rIL-12) less attractive as a cancer therapy. NHS-IL12 is a fusion protein of IL-12 and NHS76 (human IgG1) antibody engineered to target single and double stranded DNA present in necrotic areas solid tumors. In preclinical tumor models, NHS-IL12 elicited significant Th1 immune activation and tumor suppressive effects, primarily mediated by NK and CD8 + T lymphocytes, with engagement of myeloid immunity. NHS-IL12 is currently being evaluated clinically in combination with various therapeutic modalities, including chemotherapy, radiation therapy, immune checkpoint inhibition, vaccines, and epigenetic modulation. Here we review the preclinical and clinical studies involving NHS-IL12 for the treatment of solid malignancies.